How Does the Seed Pre-Germinative Metabolism Fight Against Imbibition Damage? Emerging Roles of Fatty Acid Cohort and Antioxidant Defence - Doria, Enrico; Pagano, Andrea; Ferreri, Carla; Larocca, Anna Vita; Macovei, Anca; Araújo, Susana de Sousa; Balestrazzi, Alma (Frontiers in Plant Science, 2019)
During seed imbibition, lipids are engaged in membrane reorganization while facing free radical-mediated oxidative injury. In the present work, we explored changes in lipid components at different timepoints of imbibition (0.5, 2, 4, 6, and 8 h) in the legume Medicago truncatula, by combining biochemical approaches with targeted lipidomics and untargeted metabolomics. ROS and RNS (reactive oxygen and nitrogen species) accumulation was observed throughout the tested timepoints whereas lipid peroxidation increased at 4 h of imbibition. The seed response to oxidative damage was evidenced by a significant increase in tocopherols starting from 0.5 h of imbibition as well as by the reduction in total thiol content occurring at 2 h of imbibition. Since under physiological conditions, the proper functions of the cell membranes are strongly dependent on the qualitative and quantitative balance of fatty acid residues in phospholipids, the investigation was expanded to the fatty acid cohort of Medicago truncatula seeds. Total saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), polyunsaturated fatty acids (PUFAs), omega-3 and omega-6 fatty acids showed fluctuations during seed imbibition. The most remarkable finding was the profile of the omega-3 PUFA docosopentaenoic acid (DPA, 7 cis, 10 cis, 13 cis, 16 cis, 19 cis-22:5) that showed a peak (up to 1.0% of the total fatty acid content) at 0.5 and 8 h of imbibition, respectively, concomitant with the peaks observed in tocopherol levels. It is possible that the observed changes in DPA alter the physical properties of membranes, as reported in animal cells, triggering signaling pathways relevant for the cell defence against oxidative injury. Furthermore, the content and balance between tocopherols and PUFAs is regarded as a determinant of storage stability. No enhancement in trans-fatty acids occurred throughout imbibition, suggesting for a proper antioxidant response carried by the seed. Fatty acids profiles were integrated with data from untargeted metabolomics showing changes in lipid sub-pathways, among which fatty acid amide, lyso-phospholipids and phospholipid metabolism. The emerging lipid profiles and dynamics are discussed in view of the overall imbibition damage generated during M. truncatula seed imbibition.